Confirmation of the monoclinic Cc space group for the ground state phase of Pb(Zr0.525Ti0.475)O3: A combined synchrotron X-ray and neutron powder diffraction study - Singh Solanki R.; Kumar Mishra S.; Senyshyn A.; Yoon S.; Baik S.; Shin N.; Pandey D. (My University, 2025)
The low temperature antiferrodistortive phase transition in a pseudo-tetragonal composition of Pb(ZrxTi1-x)O3 (PZT) with x = 0.525 is investigated through a combined synchrotron x-ray and neutron powder diffraction study. It is shown that the superlattice peaks cannot be correctly accounted for in the Rietveld refinement using R3c or R3c + Cm structural models, whereas the Cc space group gives excellent fits to the superlattice peaks as well as to the perovskite peaks. This settles at rest the existing controversies about the structure of the ground state phase of PZT in the morphotropic phase boundary region. © 2013 American Institute of Physics.